Universidade corporativa: uma reflexão sobre a aprendizagem organizacional e o seu valor para o indivíduo - Vivas, Marcelo Duarte (2008)
One of principal goals of this work was to investigate the reasons for the growth of Corporate University in Brazil, therefore, it is concluded that the capacitation is geared towards the improvement of the performance of the organization¿s business; the dissemination of common values in the organization includes customers, suppliers and society; The investment in the trademark of the company uses the network of people committed to the organization; and the development of the innovation¿s culture and the growth within the organization. The other main objective of this study was to identify the perception of the official in relation to the University Petrobras in training and development of the individual and its consequent increase in value. For this, 5 testimonies were collected and a field research was made with the application of a closed questionnaire considering a sample of 43 respondents, which are allocated among the states of Rio de Janeiro and Sao Paulo. The research shows that 88 % of the respondents approve the conduction of teaching/learning and consequent enhancement of human potential, in line with the strategic goals of the Company, promoted by Petrobrás Corporate University. Finally, it is concluded that the Corporative University is an institution of education and training of companies that provide several learning alternatives, aligned to organizational strategies, to promote the development not only of their staff, but also of other members of the value chain of the company, as customers, suppliers and partners.